Climate policy attitudes in consumers - Nathan Mariano (Environmental Research Letters, 2025)
Fully decarbonized markets for consumer goods would result in drastic lifestyle changes for many individuals. However, most research on climate policy attitudes focuses on energy policy, rather than policies that affect consumer goods that people use and enjoy. I conduct a survey experiment that compares views on an energy tax policy to views on a policy that taxes a high-emissions consumer good (red meat & dairy products). The results show that the effect of targeting consumer goods on support for decarbonization depends on an individual’s consumption preferences. Frequent consumers become less supportive of climate policy when it affects a particular consumer good, whereas non-consumers become more supportive. We observe the first outcome even though the cost of the two policies to consumers is equivalent, highlighting the role of subjective and identity attachments to consumer goods in policy attitudes. This shows how climate policy can favor the interests of certain consumers over others, making groups of consumers another relevant distributive cleavage in climate politics.